FAKTOR YANG MEMPENGARUHI TINGKAT KEPERCAYAAN AUDITOR EKSTERNAL TERHADAP FUNGSI AUDIT INTERNAL - , LINGGAR PUTRI PURNAMASARI, Dr. Supriyadi, M.sc., CMA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is an empirical study of one of the problems in the field of auditing , namely the relationship between the external auditor and the internal auditor during the financial audit of a company. In connection with the audit work performed by the external auditor, internal auditors can be used as a useful adjunct assistant when external auditors require additional reference in particular regarding the internal control system of the company. The question is the extent to which the external auditor can rely on the internal control performed by internal auditors? What factors are likely to influence the level of trust of the external auditor to the audit quality of the internal audit function? The purpose of this study was to determine the factors that influence the external auditorâs reliance on internal auditors during the conduct of audit work . Primary data collected in this research using questionnaires of the study sample 42 eksternal auditors who worked at the firm in Yogyakarta and tested using the test reliability and test valliditas ( Cronbach Alpha and product moment correlation). Sampling technique in this study using a convenience sampling method and analysis tool used is multiple linear regression . The results showed that of the five variables used only one factor that is background knowledge and expertise of internal auditors that generate significant positive beta on the level of trust from the external auditor to interna auditorl.